The crossroads - Grabenstein, Chris (Grabenstein, Chris. Haunted mystery., 2008)
When eleven-year-old Zack Jennings moves to Connecticut with his father and new stepmother, they must deal with the ghosts left behind by a terrible accident, as well as another kind of ghost from Zack's past.